The research was conducted in sub-district of Ciledug (Cirebon) with the objectives to study the infexiation and larvaal population development id onion armyworm. Spodoptera exigua (Habner) (Lepidoptera: Noctuidae), on shallots grown in lowland. Monitoring of egg masses and leaf damage were made at 3-4 days internal while of larvae at 1 week internal. Outbreak took place during the dry season of August-October 1995 when population density reached 0.8 egg mass and 23 larvae per hill, and subseque - Aunu Rauf (Buletin Hama dan Penyakit Tumbuhan, 1999)
The research was conducted in sub-district of Ciledug (Cirebon) with the objectives to study the infexiation and larvaal population development id onion armyworm. Spodoptera exigua (Habner) (Lepidoptera: Noctuidae), on shallots grown in lowland. Monitoring of egg masses and leaf damage were made at 3-4 days internal while of larvae at 1 week internal. Outbreak took place during the dry season of August-October 1995 when population density reached 0.8 egg mass and 23 larvae per hill, and subsequently all hills were heavily damaged. Throughout the rainy season of December 1995-February 1996, egg masses and larvae were difficult to find. Result of hand-picking showed that larval population during dry season was 78 times higher than those of rainy season. Larvae exhibited body color vartations. During the epidemics 80 percent of the larvae were dark whereas,during the endemics only 10 percent, the rest were light green. Level of egg parasitization was 0,9 percent coused by Tricogramma xp. (Hymenoptera; Trichogrammatidae) and telenomus sp. (hy menoptera; sceltonidae ), and larval parasitization 5.7 percent coused by Microplitis sp. (Hymenoptera; Braconidae), Euplectrus sp. and stenomesius sp (Hymeno[tera; Eulophidae), and Peribaea sp. (Diptera; Tachinidae). Low level of parasitization together with the abundance of food supply and dry season were believed to be the main foctors contributing to the population outbreaks. Hand-picking of egg masses and larvae conducted regularly, as practiced by the farmer group in the village of Dukuh wringin (Brebes(, should be adopted as a key activity for mitigating S. exigua infestation during dry season; and therefore, this practice should disseminated to farmers in other areas.